2001
DOI: 10.1081/iph-100108607
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Test in Patients With Multiple Drug Allergy Syndrome

Abstract: Multiple Drug Allergy Syndrome (MDAS) is a frequent clinical condition characterized by reactions to more than one different class of antibiotics. Even if some studies have previously reported an increased rate of allergic reactions to drugs in patients with a history of antimicrobials and NSAIDs allergy, risk factors and pathogenesis of MDAS are still object of investigation. Moreover, in these subjects it is often difficult to prescribe a safe alternative antibiotic without a tolerance test. In this study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Risk factors for MDIS include female sex, older age, greater weight, prior hospitalizations, and multiple medical comorbidities . Female sex has also been identified as a risk factor for MDAS . Prior studies have suggested associations between MDIS and/or MDAS and various psychiatric comorbidities, including anxiety, depression, alexithymia, and somatization .…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for MDIS include female sex, older age, greater weight, prior hospitalizations, and multiple medical comorbidities . Female sex has also been identified as a risk factor for MDAS . Prior studies have suggested associations between MDIS and/or MDAS and various psychiatric comorbidities, including anxiety, depression, alexithymia, and somatization .…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting data are available about the possibility that several individuals more likely than others might develop immediate adverse drug reactions (35–39). The case we presented of a patient reactive both to β ‐MT and pen‐G further support the existence of a multiple drug allergy syndrome also for delayed hypersensitivity (40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that multiple drug allergy syndrome is a distinct clinical entity in the adult population and that it can be detected by tolerance tests [5][6][7]. Multiple antibiotic sensitivity has been reported among the pediatric population, with the incidence ranging from 11% to 40% of selected groups of children presenting with drug allergy reported by Park et al [8] and Kamada et al [9], respectively.…”
Section: Introductionmentioning
confidence: 96%